Effect of pupil dilation on IOLMaster® measurements in Pakistani Eyes - Maqsood Ahmad Burq; Jehanzeb Khan; Sidra Zafar; Baila Shakaib; Zafar Iqbal (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the effect of pupil dilation on intraocular lens instrument IOLMaster 500 biometric measurements, and to determine the effect of these measurements on intraocular lens power calculations in Asian eyes. Methods: The prospective study was conducted at the Aga Khan University Hospital, Karachi, between January and April 2017, and comprised all patients scheduled for cataract surgery who underwent scanning with IOLMaster 500. For each patient, pre-dilation and post-dilation measurements were taken. The intraocular lens power was determined through Sanders/Retzlaff/Kraff Theoretical, Holladay, and Hoffer Q formulae. Data was analysed using SPSS 24. Results: There were 276 eyes of 138 participants who had a mean age of 59.7±11.1 years. Anterior chamber depth changed significantly with pupil dilation (p=0.001). No significant changes were observed in the axial length (p=0.410), keratometry measurements (p=0.931), and intraocular lens power calculations (p>0.05). Conclusions: The change in anterior chamber depth, though significant, was perhaps clinically non-significant. intraocular lens power did not exhibit any significant differences post-mydriasis. Key Words: Mydriasis, Lenses, Intraocular, Lens, Implantation, Phakic intraocular lenses, Biometry.